NURSING CARE PROVIDED TO WOMEN ON HEMODIALYSIS IN A HOSPITAL OF TRIÂNGULO MINEIRO - Martins, Lágila Cristina Nogueira; Pereira, Maria Elizabeth Roza; Martins, Larínia Carolina Nogueira (Journal of Health Care, 2017)
Introduction: Hemodialysis corresponds to a rigorous and continuous treatment, which brings physical and psychological limitations to patients. This way, nursing care becomes indispensable for coping with the difficulties found and adhesion to treatment. Objectives: This study aims to analyze the quality of nursing care provided to women on hemodialysis. Materials and methods: This is a descriptive, cross-sectional field research with a qualitative approach, that it was done in the hemodialysis sector of a University Hospital of Triângulo Mineiro/MG. Results: Analyzing the answers, it was possible to observe that the majority of women classified the nursing care and the information provided to them as satisfactory for their treatment. Conclusion: This way, nursing care is directed not only to avoid the complications that may be present during the hemodialysis sessions, but also to cope with the anxieties and consequent acceptance of the disease and adhesion to treatment, as well as clarification of the doubts of the patients and their relatives.